Democracy and taxation - Pavlos Balamatsias (Economics: The Open-Access, Open-Assessment E-Journal, 2018)
In this paper, the author argues that democracies increase tax revenues, based on the hypothesis that democracies increase direct and indirect taxes due to increased taxpayers' compliance, diffusion of taxes between democracies and because voters in poor democracies are in favour of import taxes. The author tests this hypothesis using data on 74 countries from 1993 to 2012. His explanatory variable is a dichotomous democracy measure, but he alters his analysis from previous research by assuming that democracy is not an exogenous variable. Instead, he uses the theory of Huntington (The third wave: Democratization in the late twentieth century, 1991) and the methodology of Acemoglu et al. (Democracy does cause growth, 2014) about democratization waves. According to this theory, democratizations occur in regional waves; consequently, diffusion of demand for or discontent with a political system is easier to happen in neighbouring countries due to economic, political and historical similarities. This measure shows us that demand for or discontent with a given political system in a geographical area, influences a country's political system and its tax choices. Using a 2SLS fixed effects model the author finds that democratization waves positively affect democracy, and in turn democracy increases direct and indirect taxes. These results remain the same using several robustness tests.
Keywords: P16; H2; 330; Democracy; political development; regional democratization waves; taxation